Relationship Between Children's Characteristics And Bullying Behaviour At Junior High School N 10 Bengkulu City In 2024 - Khairunnisa, Miska; Tranado, Hengki; Murwati, Murwati (Universitas Dehasen Bengkulu, 2025)
Bullying is one type of coercive behavior shown by overbearing behavior and repeated use of harassment or pressure to influence others. The specific objectives of this study were to to determine the frequency distribution of the correlation between the characteristics of children with bullying behavior (age, gender, play group, bullying behavior) and to know the correlation between the characteristics of age, gender, play group in children at SMP N 10 Bengkulu City in 2024. This study used a descriptive design with a cross sectional approach because researchers wanted to describe the rate of bullying behavior in the junior high school age community and determine the correlation between bullying behavior and the characteristics found in junior high school age children at SMP N 10 of Bengkulu City in 2024. The results of this study are the correlation between children's age and bullying behavior at SMP N 10 of Bengkulu City, the correlation between gender and bullying behavior at SMP N 10 of Bengkulu City, and the correlation between play groups or peers (gangs) with bullying behavior at SMP N 10 of Bengkulu City. Age with bullying behavior gets a value of p=0.200 which indicates no correlation, gender with bullying behavior gets a value of p=0.821 which indicates no correlation, play groups or peers (gangs) gets a value of p=0.029 which indicates a correlation. Schools and educational institutions including the government can see that the bullying problem that afflicts junior high school students is a real thing. This material on bullying in school children can be used as modality therapy to form a positive self-concept in school children therefore it can reduce the occurrence of bullying and can build school programs such as anti-bullying movements.